2020
DOI: 10.3390/ijms21072625
|View full text |Cite
|
Sign up to set email alerts
|

Progestins Related to Progesterone and Testosterone Elicit Divergent Human Endometrial Transcriptomes and Biofunctions

Abstract: Progestins are widely used for the treatment of gynecologic disorders and alone, or combined with an estrogen, are used as contraceptives. While their potencies, efficacies and side effects vary due to differences in structures, doses and routes of administration, little is known about their effects on the endometrial transcriptome in the presence or absence of estrogen. Herein, we assessed the transcriptome and pathways induced by progesterone (P 4 ) and the three most commonly used synthetic progestins, medr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…The strengths of this study were that it was performed ex vivo using genital mucosal samples from a well-defined group of HESN participants. To control for the influence of sex hormones, only women who were not using hormonal contraceptives were included since sex hormone levels and use of hormonal contraceptives can significantly affect the apical (E-cadherin − ) epithelial layer, as well as the genital proteome and transcriptome [ 22 , 23 , 25 , 54 , 55 , 56 , 57 ]. As the study was controlled for menstrual cycle stage, our study groups had comparable progesterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of this study were that it was performed ex vivo using genital mucosal samples from a well-defined group of HESN participants. To control for the influence of sex hormones, only women who were not using hormonal contraceptives were included since sex hormone levels and use of hormonal contraceptives can significantly affect the apical (E-cadherin − ) epithelial layer, as well as the genital proteome and transcriptome [ 22 , 23 , 25 , 54 , 55 , 56 , 57 ]. As the study was controlled for menstrual cycle stage, our study groups had comparable progesterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pharmacological effect of PR modulators and P4 antagonists has been reported to work in a cell-specific manner [ 149 ]. A study confirmed that P4 and progestins activate or repress unique genomic and proteomic profiles [ 168 ], which explains some puzzling findings in previous studies, such as that P4 uniquely affects angiogenesis while MPA affects cell migration [ 86 ]. Therefore, some conflicting outcomes are likely due to the use of different progestogen types.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, E2 priming and its combination with E2 bring changes to original regulatory patterns. Certainly, some amount of the changes come from E2-mediated signaling, which activates cognate nuclear receptor and non-genomic pathways, leading to altered proangiogenic profiles [ 86 ]. Further, more than 80% of genes regulated by E2 are regulated by progestogens, while progestogen treatment can alter more than half of E2-induced transcriptomes [ 14 ], suggesting that PR dominantly conveys an antagonist to E2-related gene expression and signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Also, in endometrial stromal fibroblasts, treatment with medroxyprogesterone acetate resulted in differential expression of almost 150 genes compared with progesterone. 29 Given these important biological differences, mechanistic studies of myometrial and leiomyoma tissue obtained from women with different exposures to DMPA are needed to investigate the biological pathways at play. Our study has limitations.…”
Section: Discussionmentioning
confidence: 99%